Integration of Library Data on Reference Books: with Service Oriented Architecture Implementation methods and (ESB) Enterprise Service Bus - Erwien Christianto (Soegijapranata Catholic University, 2021)
Libraries have an important role in mastering science and technology as well as a center for information activities. Currently, the library extends its services not only in hardcopy but also in softcopy and provides faster information retrieval capabilities. Service Oriented Architecture (SOA) provides better multi-platform integration through network infrastructure. This job is to implement SOA in a Library Information System based on Glassfish Enterprice Service Bus and MySQL database. The methods for implementing library application design using SOA and ESB are built using a business process approach with several stages (M. Weske, 2006). The application of the methodology to be implemented with SOA and ESB is built using a business process approach with the following stages: The first stage, map design for integration of library requirements, the second stage is service interface design, the third stage builds relationships between services combine services that have been previously created by interaction with other services. The fourth stage is determining the logic flow that will evaluate the service logic flow that has been created with existing business processes. The fifth stage builds scenarios for shared perceptions and refining existing processes. The results show that the design has faster search capabilities that match the needs of the library.